The Effect of Corporate Social Responsibility to Corporate Reputation on Word of Mouth Toward Customer Trust - Fauzan, Nizar (GMPI Conference Series, 2022)
Nowadays, corporate social responsibility (CSR) is essential for each consumer goods company. The company needs to improve environmental concerns to the society and enhance the corporate reputation. CSR is a crucial program to the interests of its customers, shareholders, and the ecological consequences of the business activities. CSR can play an essential role in relationships, enhancing customers' trust. This study analyzes customer perception of CSR and trust. The conceptual framework in this study has two mediating variables, including corporate reputation and word of mouth on CSR on customer trust. A causal survey design and by using quantitative method. The respondents were 160 consumers who knew the CSR programs of a consumer goods company. Then, data analysis used structural equation modeling to test the hypotheses. CSR negatively affects customer trust. Then, CSR positively influences corporate reputation and word of mouth. Moreover, this research found that reputation has a positive impact on word of mouth and trust. On behalf, the mediating effect of importance and word of mouth also positively impacts CSR and consumer trust. Thus, reputation and word of mouth could enhance suppliers' power and connect buyers.